2010
DOI: 10.1111/j.1346-8138.2010.00855.x
|View full text |Cite
|
Sign up to set email alerts
|

Community‐based epidemiological study of psychosocial effects of acne in Japanese adolescents

Abstract: In this community-based cross-sectional study, 1443 Japanese adolescents aged 13-19 years participated from two schools in Kagawa Prefecture. Students completed a self-administered questionnaire to assess the prevalence of acne, knowledge about acne, self-management of acne and emotional well-being. A five-item version of the Mental Health Inventory (MHI) subscale of the Short Form 36 was used to assess psychological health and depression status. Among respondents, 859 (59.5%) said they had acne (51.6% of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

11
53
2
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 66 publications
(67 citation statements)
references
References 16 publications
11
53
2
1
Order By: Relevance
“…Fung et al and Kubota have reported that acne tends to a ect more in females than males in Asians. 15,16 In another study Tsai et al have reported that acne is associated with the female gender which is consistent with the present study. 17 Study from Korea published by Yang et al also shows that female sex is more commonly su ered by acne.…”
Section: Discussionsupporting
confidence: 82%
“…Fung et al and Kubota have reported that acne tends to a ect more in females than males in Asians. 15,16 In another study Tsai et al have reported that acne is associated with the female gender which is consistent with the present study. 17 Study from Korea published by Yang et al also shows that female sex is more commonly su ered by acne.…”
Section: Discussionsupporting
confidence: 82%
“…Cunliffe and Gollnick reported family history in 40% and Kubota et al in 56.8% of their patients of acne vulgaris. 20,21 In our study, acne scarring was seen in 80.2% patients. Incidence of post acne scarring is observed to vary from 5.9% to 40.2%.…”
Section: Discussionsupporting
confidence: 48%
“…Incidence of premenstrual flare is reported to vary from 39.1% to 57.7% by Adityan et al, Stoll et al, Ikaraoha et al, and Kubota et al 7,[24][25][26] In the present study, irregular menses was noted in 28.9% of female patients. Similarly, irregular menses noted in earlier studies varied from 10.2% to 48%.…”
Section: Discussionsupporting
confidence: 47%
“…[4]. Kubota et al [13] studied 1,443 Japanese adolescents, and reported that 59.5% had acne; of these, 52.9% said their acne had been present for at least 1 year but did not report the rate of scarring or severe acne. However, severe acne was present in 17% of subjects in a recent study of acne treatment in Japan by Kubota et al [14].…”
Section: Discussionmentioning
confidence: 99%